THE FEATURES OF MEDIATION IN EFL CLASSROOM INTERACTION: TEACHER PERSPECTIVES - Hanna Sundari (Indonesian EFL Journal, 2020)
The classroom is a place where the teacher, as an expert and the knower, teaches students through interactions influenced by several sociocultural backgrounds. Moreover, the teacher plays a role in mediating language learning processes by providing effective mediation. In brief, mediation can be defined as all objects delivered by the teacher to mediate the students to bring their current ability to the targeted performance. This current research serves to describe the features of mediation applied by English teacher in one lower secondary school in the EFL classroom context. This qualitative-based inquiry applied classroom observation and interviews as instruments to explore how the teacher mediated language learning in the classroom particularly for beginner-level students in one private school in Jakarta. The findings showed that the features of shared intention are the most salient to be mediated. This indicates that the teacher is very concerned with helping and facilitating the students to perform tasks. In addition, in mediating values, challenges, change and competence, the teacher creates engaging classroom discourses, selects particular tasks, and nurtures a positive classroom climate. Moreover, the teacher sets herself as a mediator as well as mediation as an ideal form of behavior and language model in the class.Keywords: English; foreign language; mediation; sociocultural view.